Ứng dụng chỉ thị phân tử microsatellite trong truy xuất phả hệ quần đàn cá tra (Pangasianodon hypophthalmus) chọn giống - Thi, Phuong Dung Tran (2025)
The research used ten newly developed microsatellites markers set which were assigned offsprings to their parents on the first generation of selection on striped catfish. The result shows: (1) When analysing 50 samples of parents (G0) and 50 samples of offsprings (G1), the PCR ratio was from 98-100%, the allele number (NA) ranged from 5-14 per locus. The average Polymorphic Information Content (PIC) of microsatellites on G0 and G1 were 0.71 and 0.67, respectively. The average observed heterozygosity (HO) and expected heterozygosity (HE) all over loci were 0.73, 0.76, and 0.73, 0.71, respectively. Ten microsatellites are stable and polymorphic that are suitable for parentage analysis. (2) After makers screening, parentage analysis on 50 selective families, the initial set of nine microsatellites (excluded Pahy- 02) for parentage analysis was effective with 93.4% of offspring allocated unambiguously to their parental pairs, of which families with the father not having half- sib, 93.0% of offspring was allocated unambiguously to their parental pairs and families with the father having half-sib, 94.0% of offspring allocated unambiguously to their parental pairs. The results show that the maker set with nine microsatellites can be used in parentage analysis for the breeding program on striped catfish.